Removal Methods of Antibiotic Compounds from Aqueous Environments– A Review - Zahra Derakhshan; Mehdi Mokhtari; Fatemeh Babaei; Roya Malek Ahmadi; Mohammad Hassan Ehrampoush; Mohammad Faramarzian (Journal of Environmental Health and Sustainable Development, 2016)
Introduction: Antibiotics as a type of pharmaceutical compounds are widely used in modern medicine and veterinary industries. They enter the environment in different ways, including agricultural runoff, direct discharge of urban wastewater treatment or human waste, direct disposal of medical, veterinary industrial waste and to name but a few. Antibiotics have been able to influence the microbial population. Their continuous presence in the environment can lead to bacterial resistance and in recent years, the issue has caused serious concerns in the scientific community. Materials and Methods: Unfortunately, in spite of the extensive investigations, there is still a considerable lack of integrated and classified information to assess the environmental risks of antibiotics. Therefore, in the current study, the removal of these compounds from aqueous solutions was studied. This study was carried out on the basis of surveys accomplished in recent decades and also the ones published in databases such as Google Scholar, PubMed, Elsevier, Scopus, Springer, Magiran and SID using anti-bacterial agents, antibiotic, wastewater and removal methods as the keywords. Results: Advanced treatment processes such as ozonation, advanced oxidation, activated carbon, Nano filtration and reverse osmosis can remove higher levels of antibiotics. Conclusion: Generally, the biological and chemical processes alone are not effective for antibiotics' removal from aquatic environments while combination of advanced oxidation and biological treatment processes can effectively reduce the amount of antibiotic.